Process modelling and debottlenecking study of a vaccine production - Mohamed Safri, Nurul Huda; Mel, Maizirwan; Foo, Dominic Chwan Yee; K.S. Ng, Denny; M.L. Chew, Irene (IIUM Press, 2012)
The main objective of this work is to model and optimise a locallydeveloped Infectious Coryza (IC) vaccine production. The simulation work is performed using a commercial batch process simulator SuperPro Designer v5.5. Six debottlenecking schemes were analysed using throughput analysis and cost to benefit ratio (CBR) when the annual production is increased by 100%. Based on the economic analysis, the selected debottlenecking scheme has annual revenue of USD 240 million, with a gross margin of 9.13% and a return on investment (ROI) of 46.12%. In addition, the payback period of the selected scheme is estimated to be within three years.